Innovative Use of Fog Catchers to Mitigate Water Stress and Promote Sustainable Agriculture - Becerra Regalado, Stevin Manuel; Peña Velasquez, Pedro Isac; Licapa-Redolfo, Gladys S. (LACCEI, 2024)
The research aimed to evaluate the implementation of a fog catcher system that guarantees the quality of the captured water, ensuring its compliance with the established standards, for which a fog catcher was installed using polyethylene Raschel mesh, designed to capture water from fog. and predominant fogs in the area, specifically in the El Verde population center, in the Cajamarca region, Peru. This system demonstrated outstanding efficiency during the rainy season, capturing 140.15 liters in 16 days, with daily productions of 5.3 to 16.4 liters, it was also evaluated in the dry season, collecting 73.7 liters in the same period, with daily productions of 1.8 to 7.9 liters. The analyzes of captured atmospheric water show that the physicochemical parameters meet the values of the water quality standards for category 3, suitable for irrigation and animal drinking, without risks to health or the environment. Based on these results, the feasibility of the fog catcher is concluded as a promising technology for the sustainable management of water resources in arid and semi-arid regions, essential to support local agriculture and community well-being.